Harrison's cardiovascular medicine - Loscalzo, Joseph; Harrison, Tinsley Randolph 1900-1978 (McGraw-Hill Medical, 2013)
Featuring a compilation of chapters related to cardiovascular disorders that appear in Harrison's Principles of Internal Medicine, Eighteenth Edition, this concise, full-color clinical companion delivers the latest knowledge in the field backed by the scientific rigor and authority that have defined Harrison's. You will find content from renowned editors and contributors in a carry-anywhere presentation that is ideal for the classroom, clinic, ward, or exam/certification preparation.